Parameters of back filling material prepared from mine tailing, fly ash, and mine water - Karel Dvořák; Andrea Jančíková (Acta Polytechnica CTU Proceedings, 2024)
The article investigates the influence of mine tailing, fly ash, and mine water on strength parameters as mine paste filling material performing the strength tests on different recipes of mortar mixes with individual types of fillers and wastewater from extraction of mine tailings. Recipe is prepared in proportions corresponding to the standard mortar and compared with a reference recipe according to the fresh mortar consistency test using a shaking table according to ČSN EN 1015-3. Resulting measured values on 40 × 40 × 160 mm solids samples for which the evaluation of the volume weight was carried out in the range of 2, 7, 14, 28, 56 and 90 days according to EN 1015-10 (722400). The results showed that that it is possible to prepare relatively fluid mixtures with extremely low binder dosage. And not only the water coefficient but also the granulometry of the raw material plays an important role in the long-term strengths of samples.